Some mycomycetes from Telangana state, India - D. NAGARAJU*, C. MANOHARACHARY and (Indian Phytopathology, 2017)
This communication deals with thirty myxomycetous taxa collected and identified from different forests of Telangana state, India. This report is an addition to the previously described taxa from India.